Drug addiction problem in Poland in relation to international comparisons - Kowalczyk, Anna; Dąbska, Olga; Warchoł, Martyna; Gotowski, Rafał (Journal of Education, Health and Sport, 2017)
It is commonly assumed that increasing drug problem is caused by global and multicultural changes, as well as infiltration of trends from more developed European countries. Effects of drug abuse are alarming, among others in development of psychoses, depressive and anxiety conditions, as well as viscera defects – mainly kidneys, liver, hematopoietic necrosis. The problem of drug addiction regards also people from the sick environment, because by their behavior affects destructively on the other individuals. It is related with growing public expenditures for activities associated with the restriction of drug addiction development in Poland. Therefore it is not a surprise that this issue is widely analyzed and often brought up in social discussion. The problem of drug addiction in Poland, as in the world, assumes stronger form, and hence it is necessary to reflect over the questions concerning this addiction. An aim of the study is to describe the phenomenon of drug addiction in Poland and compare the scale of problem in relation to other European countries.